Qaraqalpaq ádebiyatında poemanıń janrlıq hám formalıq ózgesheligi - Mambetov, Q (SCIENCE and SOCIETY, 2021)
The article examines the literary genre, type, genre and genre form of poem in Karakalpak literary criticism. And also given the au-
Keywords: genre; form; kind; lyrics; epic; drama; poema